MANAGEMENT TRICHOEPITELIOMA HAIR FOLLICLE PROLIFERATION IN SHIH TZU MIX POM - Ratnasari, Ayu; Wirata, I Wayan; Wandia, I Nengah (Buletin Veteriner Udayana; Vol. 15 No. 4 August 2023DO - 10.24843/bulvet.2023.v15.i04.p08, 2022)
Dogs are well-loved pets for their intelligence and loyalty. In addition, some people also like the unique characteristics of dogs. Some like it because of its unique coat color, beautiful shape or fierce look. In this case a Shih Tzu mix Pom dog, male sex, age 6 years, and white hair, with a body weight of 6 kg. Case dogs have abnormalities in the presence of masses on the back. The owner explained that initially the dog had a small lump on the back in early 2021 and grew a mass that was getting bigger and bigger, then the dog was taken to the udayana veterinary hospital on December 21, 2021 for examination and diagnosis while the dog had a mass on its back, at the time of bathing in the house by the owner, the mass in the dog breaks, the mass emits blood and pus. Based on anamnesis, clinical signs, physical examination, and confirmed through supporting examinations in the form of routine hematological examinations with the results of an increase in lymphocytes that indicate inflammation or infection in the body, MCV (mean corpuscular volume) increases which indicates a larger red blood cell size than it should be, and low MCHC is caused due to anemia, especially hypochrome microcytic anemia as well as histopathology with the result of necrosis in the skin epidermis, hair follicle epithelial cells undergo uncontrolled proliferation, and the surface of the hair follicles is covered by thick keratin as well as for low mitotic insect. Dogs are treated surgically (excision) to remove the back period. Postoperative therapy given in the form of amoxicilin antibiotics at a dose of 0.4 ml twice a day in IM for 3 days, then continued with the administration of oral antibiotics amoxicilin with a recommended dose of 20 mg / kg BB PO twice a day for seven days, non-steroidal anti-inflammatory tolfenamic acid at a dose of 4 mg/kg BB SC once a day for five days, and surgical wounds cleaned using 0.9% NaCl, then given iodine and subsequently smeared with Gentamicin sulfate 0.1% ointment given moderately at intervals of twice a day until the wound dries. Animals showed good results in the 14-day postoperative observation characterized by surgical wounds fused and drying out and good healing occurred. As a result dog cases were diagnosed with Trichoepithelioma with a prognosis of fausta. Therapy in the form of surgical excision of tumors has been carried out and is quite effective. It is still unknown whether the disease occurs when it is maintained in a captive environment.